Framework for adaptive fluid-structure interaction with industrial applications. (1st January 2013) - Jansson, Johan; Degirmenci, Niyazi Cem; Hoffman, Johan
We present developments in the Unicorn-HPC framework for unified continuum mechanics, enabling adaptive finite element computation of fluid-structure interaction, and an overview of the larger FEniCS-HPC framework for automated solution of partial diffential equations of which Unicorn-HPC is a part. We formulate the basic model and finite element discretisation method and adaptive algorithms. We test the framework on a 2D model problem consisting of a flexible beam in channel flow, and to illustrate the capabilities of the computational framework, we show two application examples from industry and medicine. We simulate a flexible mixer plate in turbulent flow in an exhaust system where the target output is aeroacoustic quantities. The second example is a self-oscillating vocal fold configuration, where the ultimate goal is to predict how the voice is affected by physiological changes from aerodynamics. Here we give the displacement signal of a point on the folds.